CULTURE AND INCLUSION IN PRODUCT DESIGN FOR AUTISTIC WOMEN: AN ANTHROPOLOGICAL APPROACH - Setti, Gabriel Augusto Miranda (Seven Editora, 2025)
INTRODUCTION: It is true that the study of politics, that is, from what could be considered as political philosophy to what is called political science more strictly, has been going on for a long time. Countless thinkers contributed to the consolidation of this area of knowledge, from the first Greek philosophers, through Roman, medieval, and modern thinkers, to the present day, when there is already talk of a political science itself.DOI: https://doi.org/10.56238/sevened2025.018-020